Mexican Scientist Diaspora in North America: A Perspective on Collaborations With México - Gómez-Flores, Paulina; Morales-Salgado, Vicente; Maza, Angélica; Villarreal, Aline; Lara-Jacobo, Linda R.; Jiménez-Córdova, Mónica Ivette; Jiménez-Alvarez, Daniel; Hernández-Mondragón, Alma Cristal (Frontiers in Research Metrics and Analytics, 2022)
Scientific diasporas from developing countries represent an opportunity to strengthen international collaborations. These collaborations build upon the desire of members of the diasporas to establish scientific, academic, technological, and cultural exchange networks with the communities in their country of origin. While Mexico has a significant number of scientists residing abroad, particularly in North America, and most of them are committed to aid in the country's development, institutional coordination has not harnessed its benefits. In this work, we present an analysis of initiatives carried out by Mexican scientists, members of the diaspora, studying or working in the United States of America and Canada. The study is based on a set of interviews with members of this diaspora. We asked scientists about the conditions that enabled or obstructed their initiatives back in Mexico, and we discussed the role of these factors for capacity building. We also provide general recommendations to enhance contributions to the advancement of science in the country.